2020
DOI: 10.1016/j.ejpoleco.2020.101860
|View full text |Cite
|
Sign up to set email alerts
|

General or central government? Empirical evidence on political cycles in budget composition using new data for OECD countries

Abstract: Previous studies used general government data to examine whether national governments' electoral motives and ideology influenced budget composition in OECD countries. General government data includes, however, the state and local level. Using new data for general and central government over the period 1995-2016, I reexamine political cycles in budget composition. The results suggest that, both at the general and central government level, leftwing governments spent more on education and less on public services … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 61 publications
1
13
0
4
Order By: Relevance
“…On the other hand, it is suggested that right‐wing governments are more concerned with reducing inflation and appeals more towards capital owners (Cahan et al., 2019; Castro & Martins, 2021). As a result, economic growth is expected to be higher under left‐wing governments as they implement more expansionary fiscal and monetary policies (Potrafke, 2020). Meanwhile, recent empirical studies show that left‐wing governments are associated with larger expenditures, while right‐wing governments spend less, confirming the anecdotal suggestion that claims left‐wing governments are larger in size (Magkonis et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it is suggested that right‐wing governments are more concerned with reducing inflation and appeals more towards capital owners (Cahan et al., 2019; Castro & Martins, 2021). As a result, economic growth is expected to be higher under left‐wing governments as they implement more expansionary fiscal and monetary policies (Potrafke, 2020). Meanwhile, recent empirical studies show that left‐wing governments are associated with larger expenditures, while right‐wing governments spend less, confirming the anecdotal suggestion that claims left‐wing governments are larger in size (Magkonis et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence that governments increase the relative weight of education, social protection, and some sub-components of health expenditure [6], as well as variations related to government ideology [9], with the left more likely to increase spending on education and the right on public services. Several authors have also found that the electoral cycle has a special impact on social expenditure and infrastructure [10].…”
Section: Political Business Cycle (Pbc) Revisitedmentioning
confidence: 99%
“…However, general government data include data of subnational governments (states, provinces, municipalities) that the national government may not influence (e.g. Castro and Martins, 2018;Potrafke, 2019). It is therefore useful to compare how national government's characteristics influence central and general government data.…”
Section: Data and Descriptive Statistics Budgets Deficits And Public Expenditurementioning
confidence: 99%